2007
DOI: 10.1055/s-2007-966592
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade dysplasia in Barrett's esophagus has a high risk of progression

Abstract: Patients diagnosed with LGD during surveillance of Barrett's esophagus are at a considerably increased risk of progressing to develop esophageal cancer over an 8-year period but most deaths are not cancer-related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 18 publications
0
61
1
3
Order By: Relevance
“…If physicians are unable to accurately identify which patients with LGD will go on to develop HGD or EAC, surely intervention should be an option that is considered? Although most deaths are not cancer-related, a significant number of patients with LGD develop esophageal cancer [38] , which in itself is associated with significant morbidity and burden to both the patient and the healthcare system.…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%
“…If physicians are unable to accurately identify which patients with LGD will go on to develop HGD or EAC, surely intervention should be an option that is considered? Although most deaths are not cancer-related, a significant number of patients with LGD develop esophageal cancer [38] , which in itself is associated with significant morbidity and burden to both the patient and the healthcare system.…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%
“…As mentioned earlier, the definition of dysplasia is fraught with difficulties and without a well-defined uniform natural history compounded by widely varying risk estimates for progression to cancer of 0.6-1.6% [Lim et al 2007;Sharma et al 2006b;Dulai et al 2005;Shaheen et al 2000]. Therefore, it is difficult to be definite about ablative therapy in this group at this time although it in the future it can be considered as a therapeutic option especially if the high-risk population of progressors could be identified.…”
Section: Low-grade Dysplastic Barrett's Oesophagusmentioning
confidence: 99%
“…The reasons include poor interobserver correlation (reactive changes due to oesophagitis versus LGD), biopsy sampling error and regression of LGD as a result of immunosurveillance [Sharma et al 2004[Sharma et al , 2006bRajendra and Robertson, 2010]. Some authorities have estimated the incidence of OA in LGD to be between 1.7% and 14.6% per annum [Fleischer et al 2010] based on meta-analysis [Wani et al 2009] and individual studies [Skacel et al 2000;Gatenby et al 2009;Lim et al 2007;Veith, 2007]. Nevertheless, in a large multicentre study conducted by one of the authors (PS) revealed that the incidence of OA among patients with Barrett's LGD was even lower at 0.6% per year [Sharma et al 2006b].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of cost-effectivity in patients with BE, it was found that the rate of disease progression should be over 0.5% in order to make endoscopic surveillance at a frequency under 5 years (36). Although the annual progression rate of BE without dysplasia to HGD/EAC is demonstrated at different rates in studies, there is no study that shows it to be more than 0.5% (7,18,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Considering the additional risk factors such as Prague M>3, male gender, Caucasian race, advanced age, smoking history, and central obesity, it is assumed that endoscopic surveillance should be made in BE patients who do not have dysplasia due to the low rate of progression at 3-5-year intervals by taking a decision particular to the patient's characteristics.…”
mentioning
confidence: 99%
“…The annual progression rate from LGD to HGD/EAC occurred in a wide range between 1.1% and 12.8% in different studies (7,8,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Considering the annual progression rate, annual surveillance is recommended in BE with LGD.…”
mentioning
confidence: 99%